95 eRostering an Emergency – How COVID-19 forced our trust to implement eRostering within 2 weeks. (16th November 2020) - Johnson, Mark; Gardner, Stephen
Abstract : Aims: Stoke Mandeville Hospital is a district general hospital within Buckinghamshire Healthcare NHS Trust in Aylesbury, Buckinghamshire. The initial COVID-19 pandemic quickly showed that the Trust's understanding of its medical workforce deployment was suboptimal. With doctors redeployed from other services, increased sickness and COVID-19 self-isolation, current manual rostering proved insufficient. Trainees reported that unequal deployment was impacting their workload and morale. eRostering was proposed as a solution. Methods: The software chosen (HealthRota) was previously reviewed by the Trust's Junior Doctors' Forum. The solution offered limited contractual tie-in at low cost, so was approved by the Trust and rolled out quickly to support the COVID-19 response. The initial 'back end' rollout of medical on-call rotas and supplementary departments was completed in three days. Within two weeks, all end users had logins to view their rotas and the availability of the wider medical team. Results: The solution's effectiveness was determined by feedback from the rota coordinators and questionnaires from clinicians. Within a month of launch, 95% of junior doctors had used the software and 60% had used the mobile application. Their reported understanding of colleagues' deployment was significantly improved. Rota coordinators supported the change, reporting a greater overview of staffing and lower dependency on locums. Conclusions: eRostering can be implemented at pace and efficiency does not mean a reduction in quality of the eventual solution, especially if there is early stakeholder engagement. The rapid, successful deployment of eRostering software during the COVID-19 pandemic shows how an agile healthcare organisation can act decisively to implement new IT solutions faster than previously thought possible. eRostering saves time, but to benefit fully rota coordinators need to adjust deployment on a daily basis and must be adequately resourced.